2015
DOI: 10.18632/oncotarget.3449
|View full text |Cite|
|
Sign up to set email alerts
|

Connexin 43 expression is associated with increased malignancy in prostate cancer cell lines and functions to promote migration

Abstract: Impaired expression of connexins, the gap junction subunits that facilitate direct cell-cell communication, have been implicated in prostate cancer growth. To elucidate the crucial role of connexins in prostate cancer progression, we performed a systematic quantitative RT-PCR screening of connexin expression in four representative prostate cancer cell lines across the spectrum of malignancy. Transcripts of several connexin subunits were detected in all four cell lines, and connexin 43 (Cx43) showed marked elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 36 publications
6
58
0
Order By: Relevance
“…While both A-375 and NIH/3T3 presented a significant inhibition of 30% and 46%, respectively, with 10 μM Carbenoxolone, LLC cells demonstrated no clear effect on proliferation (Supplementary Figure 2). Our results support previous experiments that presented a lack of response in human prostate cell lines which were incubated with considerably higher concentrations of Carbenoxolone over 7 days [39]. Data suggest that rather than affecting proliferation, the main mechanism through which the drug acts in these cells is through targeting other metastatic cellular processes related to cell migration and invasion.…”
Section: Discussionsupporting
confidence: 91%
“…While both A-375 and NIH/3T3 presented a significant inhibition of 30% and 46%, respectively, with 10 μM Carbenoxolone, LLC cells demonstrated no clear effect on proliferation (Supplementary Figure 2). Our results support previous experiments that presented a lack of response in human prostate cell lines which were incubated with considerably higher concentrations of Carbenoxolone over 7 days [39]. Data suggest that rather than affecting proliferation, the main mechanism through which the drug acts in these cells is through targeting other metastatic cellular processes related to cell migration and invasion.…”
Section: Discussionsupporting
confidence: 91%
“…The authors suggested this was due to enhanced intravasation and extravasation, as Cx26 facilitated heterologous GJIC between melanoma cells and endothelial cells ex vivo . Several other studies now suggest that increased connexin expression within the tumour (and even in the tumour stroma 133 ) at late stage disease facilitates metastatic features such as migration and invasion 134-137 (reviewed in 63 ), endothelial adhesion 138,139 , intravasation and extravasation 132,139-143 , and targeting to the metastatic site 144 . In addition, a recent study clearly demonstrates how Cx43 can increase growth of brain metastases at a very late stage, after extravasation and remodelling of existing vascular networks 145 .…”
Section: Reassessing Connexins In Cancermentioning
confidence: 99%
“…Besides cadherins, Ig superfamily members and ephrins/EpH receptor systems were implicated in mediating more labile or transient cell-cell interactions in cancer cells (Cavallaro and Christofori 2004;Haeger et al 2014;Krusche et al 2016). As well, connexins may enable communication through GJs between connected tumor cells and their inhibition reduces collective migration in prostate cancer cells (Zhang et al 2015). Similar to morphogenetic and homeostatic migration, collectives of migrating cancer cells display leader cells that engage with surrounding tissue structures via Rac-driven filopodal protrusions and integrin-mediated substrate adhesion (Hegerfeldt et al 2002;Yamaguchi et al 2015).…”
Section: Collective Cell Migration By Cell -Cell Junction Regulationmentioning
confidence: 99%